2004
DOI: 10.1111/j.1728-4457.2004.012_1.x
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Gender Equity in India: Examining Dyson and Moore's Thesis with New Data

Abstract: In revisiting the influential Dyson and Moore (1983) hypothesis as to why women in South India enjoy relatively more agency than in the North, we conducted an econometric analysis of the determinants of women's mobility and decisionmaking authority. Data for the study come from a household data survey carried out in the Northern state of Uttar Pradesh and in the Southern state of Karnataka in 1995. We find that cross-cousin and uncle-niece marriage is more prevalent in Karnataka as expected. Contrary to Dyson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(144 citation statements)
references
References 20 publications
9
130
4
1
Order By: Relevance
“…The findings support the empirical analysis of Rahman & Rao in 2004, that women's autonomy is not solely a reflection of kinship structures. 21 Public services such as family planning may have an important, transformative effect on familial power relations, making it possible for young couples to make autonomous choices about spacing children.…”
Section: Discussionsupporting
confidence: 79%
“…The findings support the empirical analysis of Rahman & Rao in 2004, that women's autonomy is not solely a reflection of kinship structures. 21 Public services such as family planning may have an important, transformative effect on familial power relations, making it possible for young couples to make autonomous choices about spacing children.…”
Section: Discussionsupporting
confidence: 79%
“…On the contrary, girls aged below 3 y were more likely than boys to be underweight and stunted in the South than in the North. In addition, it has been suggested that economic and political factors, including political will, are more important than kinship structures in patterning gender differences between North and South India (Rahman & Rao, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hashemi, Schuler and Riley, 1996 find that physical mobility improves the degree of control over microcredit loans, since it reflects a woman's access to outside employment opportunities. A study of the determinants of female autonomy in India finds that a better-educated woman has greater bargaining power, as measured by physical mobility and say in household resource allocation, through the channel of increased information (Rahman and Rao, 2004). The same study also finds culture, as measured by state fixed-effects, to significantly increase bargaining power despite controlling for religion and caste.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Another section of the literature finds that a woman's access to employment outside the house increases her household bargaining power (for a study in Bangladesh, see Anderson and Eswaran, 2009; for a study in India, see Rahman and Rao, 2004). The ownership of assets, in particular, is one important way through which access to employment helps empower women in developing countries (for example, see Agarwal, 2001, for evidence from India).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation